Implementation of Inquiry-Based Interactive Games to Improve Interest and Science Learning Outcomes in Human Reproductive System Material: Penerapan Game Interaktif Berbasis Inkuiri untuk Meningkatkan Minat dan Hasil Belajar IPA Materi Sistem Reproduksi pada Manusia - Fitria Nur Aini; Supardi U. S. (Institute of Advanced Knowledge and Science, 2024)
This research was motivated by students' perception that Science lessons are difficult to understand and boring due to the one-way teaching method, which has led to a decline in student interest and learning outcomes. The purpose of this research was to increase the interest and learning outcomes of ninth-grade students in class 9.3 at SMP Negeri 2 Cisauk. The research method used was Classroom Action Research. Data collection techniques involved quantitative data from learning outcomes and qualitative data through analyzing interest questionnaire sheets. The results show an increase in students' learning interest and outcomes. The percentage of students' interest in learning before and after the intervention increased from 54,5% to 93,9%. The average learning outcomes of students increased from 62,5 to 79,3. This research shows that inquiry-based interactive games on the Human Reproductive System material led to an increase in students' interest and learning outcomes.